Material Recycling in Transport - Štrumberger, Nada; Jurum Kipke, Jasna; Štefančić, Gordana (Promet - Traffic&Transportation, 2012)
Recycling means re-introducing waste material into theproduction process, as addition to primary resources. The useof waste as secondary raw material is economically justified. Byusing old material not only primary raw material is saved, butenergy as well.The paper presents the most frequent materials, the ways inwhich they are collected, and subsequent classification. Thesorting procedures have been mentioned, with throughput capacityan imp01tant parameter expressed in tonnes per hour.The higher the throughput capacity, the better the effect of sorting.